2018
DOI: 10.7554/elife.38689
|View full text |Cite
|
Sign up to set email alerts
|

PIP2 depletion promotes TRPV4 channel activity in mouse brain capillary endothelial cells

Abstract: We recently reported that the inward-rectifier Kir2.1 channel in brain capillary endothelial cells (cECs) plays a major role in neurovascular coupling (NVC) by mediating a neuronal activity-dependent, propagating vasodilatory (hyperpolarizing) signal. We further demonstrated that Kir2.1 activity is suppressed by depletion of plasma membrane phosphatidylinositol 4,5-bisphosphate (PIP2). Whether cECs express depolarizing channels that intersect with Kir2.1-mediated signaling remains unknown. Here, we report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 54 publications
5
127
0
Order By: Relevance
“…Interestingly, blocking of PLC by U73122 also reduced the slow global Ca 2+ response (i.e., TRPV4‐mediated Ca 2+ influx). Previous work has shown that TRPV4 channels are inhibited by the phospholipid, phosphatidylinositol 4,5‐bisphosphate (PIP 2 ; Harraz, Longden, Hill‐Eubanks, & Nelson, ). PLC‐mediated depletion of PIP 2 results in disinhibition of TRPV4 channels and increased Ca 2+ influx (Harraz et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, blocking of PLC by U73122 also reduced the slow global Ca 2+ response (i.e., TRPV4‐mediated Ca 2+ influx). Previous work has shown that TRPV4 channels are inhibited by the phospholipid, phosphatidylinositol 4,5‐bisphosphate (PIP 2 ; Harraz, Longden, Hill‐Eubanks, & Nelson, ). PLC‐mediated depletion of PIP 2 results in disinhibition of TRPV4 channels and increased Ca 2+ influx (Harraz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that TRPV4 channels are inhibited by the phospholipid, phosphatidylinositol 4,5‐bisphosphate (PIP 2 ; Harraz, Longden, Hill‐Eubanks, & Nelson, ). PLC‐mediated depletion of PIP 2 results in disinhibition of TRPV4 channels and increased Ca 2+ influx (Harraz et al, ). Thus, blocking of PLC by U73122 might be expected to decrease TRPV4 channel activity.…”
Section: Discussionmentioning
confidence: 99%
“…Channel inhibition is released following G q ‐protein‐coupled receptors (G q PCR) activation and downstream PIP 2 depletion. Importantly, PIP 2 was also shown to regulate inwardly rectifying potassium (Kir) channels (Harraz, Longden, Dabertrand, Hill‐Eubanks, & Nelson, ; Harraz, Longden, Hill‐Eubanks, & Nelson, ). Together, these studies support the notion that aberrant TRPV4‐mediated signaling may result in both astrocyte and vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…While not specifically addressed in this study, elevated basal astrocyte Ca 2+ in hypertensive mice may interfere with the molecular mechanism that drives the NVC response and/or are involved in the clearance of metabolic by‐products (e.g., glymphatics; Iliff et al, ; Iliff et al, ). The recent evidence in capillary endothelial cells demonstrating a dynamic interaction between TRPV4 and Kir2.1 channels, whereby GqPCR activation induces PIP 2 depletion, a master regulator of both channels (Harraz, Longden, Dabertrand, et al, ; Harraz, Longden, Hill‐Eubanks, & Nelson, ; Longden et al, ) raises an important question. Could augment Ang II‐mediated signaling impair TRPV4‐Kir2.1 interactions?…”
Section: Conclusion and Functional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation